2010
DOI: 10.1159/000273067
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in <i>NOS3, ACE </i>and<i> PAI-1</i> Genes and Risk of Spontaneous Recurrent Miscarriage in the Gaza Strip

Abstract: Objective: This study was conducted to investigate the correlation between spontaneous recurrent miscarriage (RM) and common polymorphisms in angiotensin-converting enzyme (ACE), plasminogen activator inhibitor 1 (PAI-1) and endothelium-derived nitric oxide synthase 3 (NOS3) genes among women experiencing RM in the Gaza Strip. Methods: The presence of these genetic profiles was determined for 100 women who had had at least 3 constitutive abortions and 100 controls without any history of abortion using molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 57 publications
1
33
1
Order By: Relevance
“…This suggests a possible role for ethnic differences as a result of genetic backgrounds and the environment. The same results were proposed by Shufang Zhang et al [36] and Ozturk Ozdemir et al [37] in their recent work, even though the incompatible viewpoints were revealed by other studies [32,33,35]. In addition, because the frequency of allele could affect the results of genetic association studies, the genetic background of RPL was evaluated.…”
Section: Subgroups Results and Sensitivity Analysismentioning
confidence: 52%
See 2 more Smart Citations
“…This suggests a possible role for ethnic differences as a result of genetic backgrounds and the environment. The same results were proposed by Shufang Zhang et al [36] and Ozturk Ozdemir et al [37] in their recent work, even though the incompatible viewpoints were revealed by other studies [32,33,35]. In addition, because the frequency of allele could affect the results of genetic association studies, the genetic background of RPL was evaluated.…”
Section: Subgroups Results and Sensitivity Analysismentioning
confidence: 52%
“…While reading the full texts, the following articles were removed: two studies did not meet Hardy-Weinberg equilibrium (P 0 0.0003 and P 0 0.0217, respectively) [25,26]; one study could not extract the allele data (ACE I/D in RPL) from its groups [27]; one study was not only focused on RPL, but also on pre-eclampsia and foetal growth restriction which made it hard to get the data required [28]; and the other two studies included the data of case and control groups, but little information about the ACE I/D polymorphism [16,29]. Finally, there were 9 studies meeting the inclusion criteria that were included [11,[30][31][32][33][34][35][36][37]. Among the collected studies, five investigated Caucasian populations [11,30,31,34,37], and the others investigated Asian patients [33,34,36,37].…”
Section: Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelial nitric oxide synthase activity has been studied in the context of implantation and maintenance of pregnancy. Given this, few studies have attempted to study the polymorphisms within this gene in RM cases [52][53][54]. Only Shin et al could demonstrate a positive association of this gene with RM among their cohort of Korean women [53].…”
Section: Other Genetic Markersmentioning
confidence: 99%
“…In the literature there are some reports on the association between eNOS gene polymorphisms and IRM. However, the results of these studies have been controversial among different ethnic groups (6)(7)(8)(9)(10)(11). In this study we aimed to determine whether eNOS gene polymorphisms are associated with an increased risk for IRM in the Turkish population and to evaluate the association between NO levels and eNOS gene polymorphisms in women with IRM.…”
Section: Introductionmentioning
confidence: 97%